Antigen-receptor induced clonal expansion and deletion of lymphocytes are impaired in mice lacking HS1 protein, a substrate of the antigen-receptor-coupled tyrosine kinases. - Taniuchi, I (1995)
HS1, an intracellular protein expressed specifically in hematopoietic cells, is rapidly tyrosine phosphorylated after cross-linking of antigen receptors on B and T lymphocytes, implicating involvement of this molecule in the signal transduction pathways from the antigen receptors as a substrate of membrane-associated tyrosine kinase(s). The development of lymphoid cells in HS1-deficient mice, generated through gene targeting, appeared normal. However, antibody production to T-independent antigen and proliferative responses of splenic B and T cells after cross-linking of the antigen receptors were impaired in these mutant mice. Furthermore, B cells in the peritoneal cavity of the mutant mice were resistant to multivalent cross-linking of the antigen receptor, which causes apoptosis of such cells in normal mice. Crossing the HS1-deficient mice with the mice harboring transgenes encoding alpha and beta chains of T-cell antigen receptor against a male H-Y antigen resulted in a progeny that demonstrated a significantly impaired ability of thymic negative selection. These results indicate that HS1 is a novel molecule involved in the antigen-receptor-derived signaling pathways and plays important roles not only in clonal expansion, but also in clonal deletion of B and T cells.